Forecasting, foresight and planning for technology and socioeconomic development the Philippine setting - Diaz, Ernest Albert A.; Imbang, Glen (Quezon City University of the Philippines Diliman, 2014)
Technology plays an important role in promoting socioeconomic development as illustrated by quantitative models and by the experiences of different states of the world. South Korea, Taiwan, China and Japan are testaments to how technology can improve the socioeconomic plight of a nation. The Philippines on the other hand, despite having started from a position of advantage compared to some other Asian states, is currently lagging behind in terms of development as reflected by the low growth of it productivity over the years. This raises the question on why can't the Philippines like some of its Asian neighbors, utilize technology to achieve the socioeconomic progress they have attained. One possible angle where the answer can be found is the planning process undertaken by the Philippines. Whereas most of its Asian neighbors have put a premium on utilizing foresight activities to guide its socioeconomic plans, the Philippines conducts foresight exercises in small isolated packets with no major uptake. This study compared the foresight activities of different countries and came to the conclusion that foresight activities helped nations, whose socioeconomic progress is anchored on the exploitation of technology, plan for the effective leverage of technology to promote economic growth. With the experience of other countries on the use of the foresight process, the study was able to identify certain aspects of their foresight activities as being compatible with the Philippine setting. Thus, the study concludes that the Philippines may benefit socioeconomically by emulating some of the steps taken by select countries with regards to the use of foresight exercise to help for planning the use of technology.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Forecasting; Foresight; Planning; Socioeconomic status -- Economic condition